Ideology versus practicality : a case study in rural education : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Ball, Teresa (Massey University, 1988)
This case study attempts to provide a historical account of the first twenty five years of Feilding Agricultural High School. This coincided with the Principalship of L.J.Wild. The School curricula was sexually differentiated and chiefly aimed at providing courses which prepared rural boys and girls for their future vocations as Farmers and Farmers' wives. During the period 1922-1946, a polarity of expectations was apparent in post-primary education. The producers of rural education were endeavouring to foster knowledge thought appropriate to rural consumers. However, rural consumers were demanding an academic knowledge unrelated to rural life as it conferred social and educational advantages. Whilst Wild deplored the hegemony of the academic tradition, he was compelled to reproduce it. If he had not compromised between demands for a successful agricultural course made by the Department of Education and those for an academic course from the parents of his pupils, Feilding Agricultural High School would not have survived its first three years. Wild early realised that if he was to serve the Feilding community effectively, he would have to offer a multilateral and comprehensive form of education. This research has been undertaken from a historical perspective.
Keywords: New Zealand; Education; Feilding Agricultural High School; Rural Education; History